High throughput Luminex beads based multiplex assay for identification of six major bacterial pathogens of mastitis in dairy animals - Shrinet, Garima; Chhabra, Rajesh; Sharma, Archana; Batra, Kanisht; Talukdar, Saurabh Jyoti; Maan, Sushila (Frontiers in Cellular and Infection Microbiology, 2023)
Bovine mastitis, a multi-etiological disease of dairy animals is represented as mixed infection by over 150 different microorganisms. However, the majority of cases are produced by a relatively small group, comprising of Staphylococcus aureus, Streptococcus agalactiae, Streptococcus dysgalactiae, Streptococcus uberis, E. coli and Klebsiella pneumoniae. Specific identification and quantification of multiple bacteria in a single milk sample becomes essential for rapid intervention. In the present study a Luminex beads based multiplex assay emphasizing on the precise identification of six major bacterial pathogens of mastitis was developed. Assay was developed in two triplex sets, triplex 1 comprised of Streptococcus agalactiae, Streptococcus dysgalactiae and Streptococcus uberis while triplex 2 consisted of Staphylococcus aureus, E. coli and Klebsiella pneumoniae. The analytical sensitivity was 106 copies per reaction mixture for all the six bacteria. A 100 % analytical specificity was observed for simultaneous detection of these bacteria. Clinical milk samples from 100 bovine quarters were tested for validation. The percent agreement between the beads based multiplex assay and PCR results were 100 for all isolates. The developed Luminex beads based multiplex assay indicates a concept proof of a rapid, cost effective high throughput diagnostic tool for identification of major bacteria causing mastitis in dairy animals.